Power quality improvement by dynamic voltage restorer and unified power quality conditioner using fuzzy ligic [electronic resource] - Faridullah Kakar, 1972-, author (2015)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2015